Evaluating the thermal comfort properties of Rize's traditional hemp fabric (Feretiko) using a thermal manikin - Tama, Derya (2020)
In the present research, the thermal properties of the traditional fabric of the Rize city (Turkey) were investigated. A Feretiko, which is a fabric produced from hemp fibers at handlooms, were chosen and the thermal properties were evaluated via thermal manikin as well as the Alambeta tester and Air permeability tester. The thermal manikin tests were performed at 23 degrees C +/- 1 constant ambient temperature and 75 +/- 5% relative humidity regarding to the past annual average temperature and relative humidity data of Rize city were considered. The thermal resistance of Feretiko was measured 0.011 m(2)K/W by Alambeta tester and the total clothing insulation of the shirt manufactured from Feretiko was measured as 0.032 m(2)K/W by thermal manikin. Moreover, in ASHRAE Standard 55-2013, the clothing insulation of a long-sleeve shirt ensemble stated as 0.25 clo. The clothing insulation of the shirt manufactured from Feretiko was 0.20 clo, which is close to the value stated in the standard. (C) 2019 Elsevier Ltd. All rights reserved. Selection and peer-review under responsibility of the scientific committee of the 4th International Conference on Natural Fibers - Smart Sustainable Materials.